Effect of Pr3+ substitution at the a-site on the structural and electrical properties of hole-doped La-Based Manganites / Rozilah Rajmi ... [et al.] - Rajmi, Rozilah; Ibrahim, Norazila; Shamsuddin, Suhadir; Md Salleh, Shahrulnizam; Othman, Muhamad Hazri (Research Management Institute (RMI), 2024)
In this study, the effect of praseodymium substitution at La-site on structural and electrical transport properties of La0.5Ba0.5MnO3 was investigated. Polycrystalline La0.5-xPr0.5x Ba0.5MnO3 (x = 0, 0.50, 1.00) were synthesized using a conventional solid-state method. The powder X-ray diffraction patterns show a single-phase orthorhombic distorted perovskite structure with space group Pnma. The Rietveld refinement analysis showed that the unit cell volume decreased as Pr3+ substitution increased which may be attributed to the different ionic radii of ions. Electrical resistivity measurements by using standard four-point probe resistivity measurement in a temperature range of 30 K to 300 K. As the Pr3+ concentration increases, metal-insulator transition, TMI decreases from 264K (x=0) to 157K (x=1.00) while resistivity increases from 1.16 Ω.cm (x = 0) to 20.3 Ω.cm (x =1.00). The decreased TMI are attributed to the decrease in tolerance factor which indicates enhancement in MnO6 octahedral distortion consequently reduce double exchange interaction. The electrical resistivity in the metallic region for all samples was fitted with the combination of domain/grain boundary, electron-electron, electron-magnon and electron-phonon scattering processes. The resistivity behaviour in the insulating region for all samples was attributed to small polaron hopping model which revealed that the activation energies increased as Pr3+ content increased due to the enhancement in the distortion of MnO6 octahedral.